Chemical composition and antibacterial activity of the essential oil of Thymus ciliatus growing wild in North Eastern Algeria - Sonia HENI, Salima BENNADJA, Abdelghani DJAHOUDI & (Journal of Applied Pharmaceutical Science, 2015)
The essential oil extracted from the aerial parts of Thymus ciliatus harvested in the region of Tawra (North-East of Algeria) gave a yield of 2.5%. Its analysis by GC / MS has allowed the identification of twenty- four elements, mainly phenols and terpenes. The main components were: Thymol (67.78 %), p- cymene (12.25%), pseudo- limonene (5.10 %), and γ-terpinène (4.42 %). Antimicrobial activity was evaluated on two pathogenic foodborne bacterial strains: Bacillus cereus and Listeria monocytogenes. These pathogens showed high sensitivity with respect to the essential oil with respective inhibition diameters of 28.6and 40mm of relatively low MICs of 0.18mg / ml. Due to these results, we may propose the use of this natural substance as a substitute for additives used in food protection.
Keywords: Thymus ciliates, Essential oil, Antibacterial activity, Bacillus cereus, Listeria monocytogenes.